СТРУКТУРА И ДИНАМИКА ГЛАВНОГО МАГНИТНОГО ПОЛЯ ЗЕМЛИ НА ЕЕ ПОВЕРХНОСТИ И В БЛИЖНЕМ КОСМОСЕ - Орлюк, М. И.; Роменец, А. А. (Одеські астрономічні публікації, 2011)
Determination of space-temporal structure of the Earth’s magnetic field (EMF) on its surface and in near space is extremely necessary and actual, in connection with its influence on the character of passing of processes in magnetosphere and ionosphere, and on mechanisms and magnetic activity intensity, which are considered as a substantial ecological factor.